2005
DOI: 10.1111/j.1526-4610.2005.05177.x
|View full text |Cite
|
Sign up to set email alerts
|

Acetaminophen, Aspirin, and Caffeine Versus Sumatriptan Succinate in the Early Treatment of Migraine: Results From the ASSET trial

Abstract: The combination of acetaminophen, aspirin, and caffeine was significantly more effective (P > .05) than sumatriptan in the early treatment of migraine, as shown by superiority in summed pain intensity difference, pain relief, pain intensity difference, response, sustained response, relief of associated symptoms, use of rescue medication, disability relief, and global assessments of effectiveness. An additional, larger clinical trial is needed to confirm these results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
91
0
3

Year Published

2005
2005
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 75 publications
(96 citation statements)
references
References 25 publications
(38 reference statements)
2
91
0
3
Order By: Relevance
“…The X-ray structure of a crystal obtained from a so- 2 ] BF 4 and a-methyl itaconate ( Figure 5) further supports this pathway.…”
Section: Resultssupporting
confidence: 58%
See 2 more Smart Citations
“…The X-ray structure of a crystal obtained from a so- 2 ] BF 4 and a-methyl itaconate ( Figure 5) further supports this pathway.…”
Section: Resultssupporting
confidence: 58%
“…The investigation of the conversion of itaconic acid 2 ] BF 4 at ambient temperature under an argon atmosphere showed that the solution decolorized within minutes from orange via yellow to almost colorless (an observation that was also made with Me-DuPHOS as ligand and during hydrogenations). Due to the fast transformation, the only state that could be investigated was the one in which the decolorization was already completed.…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…Patients' most commonly given reasons for preferring triptans were effective relief, speed of relief, restored ability to function and fewer side effects [16,18,19,22]. These are significant results, as some controlled clinical trials have shown that sumatriptan was not superior to rapid-release tolfenamic acid [43], paracetamol/domperidone [44], aspirin/metoclopramide [45,46], isometheptene/paracetamol/dichlorphenazone [47] and paracetamol/aspirin/caffeine [48]. In contrast, a controlled clinical trial showed that oral sumatriptan 100 mg was significantly superior to oral ergotamine plus caffeine [49].…”
Section: Discussionmentioning
confidence: 99%
“…In the early treatment of migraine, OTC medications are largely used as they do not require a medical prescription and are easily available. A combination of OTC medications (Aspirin 500 mg, acetaminophen 500 mg and caffeine 130 mg) has been compared to a prescription migraine product (sumatriptan 50 mg), underlining a significant efficacy of this association in early migraine abortive treatment [36]. A similar approach has not been investigated yet in TTH, but pain relief as a result of rapid intake seems a reasonable suggestion.…”
Section: Aspirin and Headachementioning
confidence: 99%